Energetic Data Security Management Scheme using Hybrid Encryption Algorithm over Cloud Environment - et.al, Quazi Warisha Ahmed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now-a-days all documents are in a digital format as well as everyone need to maintain their data in electronic mode with the help of cloud servers. A cloud server provides lots of facilities to users such as remote data maintenance, huge data handling and so on. But in the case of security many cloud servers are providing probabilistic results alone. So, that a new cloud server data maintenance scheme is required to provide a high-level data security to the cloud system in an efficient manner. This paper introduces a new crypto-approach called Novel Hybrid Encryption Mode (NHEM), in which this algorithm integrates several latest approaches of crypto logics into it and provides a top-end security level to the cloud data. This NHEM is derived from the base factors of two cryptographic algorithms called Advanced Encryption Standard with 512-bit size of key frequency with Message Digest (MD5) algorithm. By using the integration of these two powerful approaches, a novel approach called NHEM is designed and it provides a huge support to preserve security on cloud medium. The cloud data needs to be protected from unwanted threats and intruders by means of raising an interruption attacks on server. The proposed approach of Novel Hybrid Encryption Mode concentrates more on access control logics and the crypto norms with respect to privacy measures. In this paper, the proposed scheme assures the data is too robust and no one can attack the data without proper credentials as well as the outcome proofs are clearly given on the resulting unit of this paper. The Advanced Encryption Standard algorithm is a well-known and powerful crypto scheme and the MD5 algorithm is also considered to be the unique unidirectional algorithm to provide security level in energetic manner. These two algorithms are combined together with the bit frequency of 512 to achieve the highest accuracy levels in data security over cloud environment as well as the resulting portion clearly illustrates that with proper graphical outcome.